Historical overview of Islam evolution in Soviet Kazakhstan - Mustafayeva, А. А. (Journal of Oriental Studies, 2016)
The paper describes the evolution of Islam in Soviet Kazakhstan from 1917 to 1991. On the basis of various documents, includingdecrees, resolutions, there was done a historical overview of the development of relations between the state and religion, the statereligion of the Kazakh people, and an overview of stages and results of persecution and support the totalitarian system of religion.